COVID-19 Vaccines: Current Status and Implication for Use in Indonesia - Youdiil Ophinni; Anshari Saifuddin Hasibuan; Alvina Widhani; Suzy Maria; Sukamto Koesnoe; Evy Yunihastuti; Teguh H Karjadi; Iris Rengganis; Samsuridjal Djauzi (Acta Medica Indonesiana)
The coronavirus disease 2019 (COVID-19) has inflicted catastrophic damages in public health, economic and social stability—putting life globally on hold in 2020 and presumably a year more. Indonesia bears a heavy burden of the pandemic, counting the highest case prevalence and fatality rate in all of Southeast Asia. One hope remains in the groundbreaking universal effort in search of a vaccine against the causative virus SARS-CoV-2, which has shown success unparalleled in human vaccine development thus far. An array of modalities including novel techniques are being utilized as vaccine platforms, with the closest to phase III clinical trial completion being mRNA (manufactured by Moderna and BioNTech/Pfizer), inactivated virus (Sinovac, Sinopharm), viral vector (Oxford/AstraZeneca, Gamaleya, Janssen/Johnson&Johnson, CanSino), and protein subunit (Novavax). The vaccine produced by BioNTech/Pfizer has been deployed to the public as the first ever licensed COVID-19 vaccine. In this review, we will review all of these modalities on their safety and immunogenicity, phase II/III trial results of the nine vaccine candidates and current situation as of 29 December 2020, as well as the implication for use and distribution in Indonesia. COVID-19 vaccine progress, however, is moving exceedingly fast and new advances are unfolding on a daily basis, to which we hope an update to this review can be published in early 2021.